2003
DOI: 10.1111/j.1550-7408.2003.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genes of Mitochondrial Origin in the Genus Entamoeba

Abstract: The amitochondriate protistan parasite Entamoeba histolytica has lost most mitochondrial functions secondarily but has retained a reduced organelle of mitochondrial origin, the mitosome. We here investigate the presence, origins, and expression in other species of Entamoeba of three genes of mitochondrial origin--pyridine nucleotide transhydrogenase and the mitochondrial-type chaperonins cpn60 and hsp70. The genes appear to be present in all species and specifically related, confirming that the E. histolytica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This would argue that sequence divergence between the amoebozoa and opisthokonts is not a barrier to detection of components of the mitochondrial import pathway. However, while the related amoeba E. histolytica has mitosomes with clear matrix-located chaperones and Tom40 and Sam50 proteins to serve in a TOM and SAM complex, further import machinery was not detectable (Tovar et al 1999;Bakatselou et al 2003;Tovar et al 2007;Likić et al in press). …”
Section: Mitochondrial Protein Import (A) Occurrence Of Protein Importmentioning
confidence: 99%
“…This would argue that sequence divergence between the amoebozoa and opisthokonts is not a barrier to detection of components of the mitochondrial import pathway. However, while the related amoeba E. histolytica has mitosomes with clear matrix-located chaperones and Tom40 and Sam50 proteins to serve in a TOM and SAM complex, further import machinery was not detectable (Tovar et al 1999;Bakatselou et al 2003;Tovar et al 2007;Likić et al in press). …”
Section: Mitochondrial Protein Import (A) Occurrence Of Protein Importmentioning
confidence: 99%
“…Some, such as those of Entamoeba and Cryptosporidium, have been shown to contain chaperonin Cpn60, a protein known to participate in the refolding of imported proteins (Sigler et al, 1998; Mai et al, 1999;Tovar et al, 1999;Riordan et al, 2003); mitosomes of Trachipleistophora contain a mitochondrialtype Hsp70 (mtHsp70), a molecular motor that helps internalize proteins into the organelle (Matouschek et al, 2000;Williams et al, 2002). Other proteins have also been suggested as putative mitosomal components in various amitochondrial lineages but their cellular localization has not been demonstrated experimentally (Clark & Roger, 1995;Bakatselou et al, 2000Bakatselou et al, , 2003Katinka et al, 2001;Morrison et al, 2001;Zhu & Keithly, 2002;Arisue et al, 2002). Perhaps the most significant finding in relation to the biology of mitosomes is the direct demonstration that Giardia mitosomes function in the biosynthesis of molecular iron-sulphur (Fe-S) clusters and in their subsequent incorporation into functional Fe-S proteins (Tovar et al, 2003).…”
mentioning
confidence: 99%
“…b Simian E. histolytica-like strainspecific block insertions. c EHMfas1-specific block insertion and 5.8S rDNA with ITS 1 and ITS 2 and Cpn60 and PNT genes of EHMfas1 and P19-061405 have been used for previous phylogenetic studies of the genus Entamoeba (Clark and Diamond 1997;Silberman et al 1999;Som et al 2000;Bakatselou et al 2003;Clark et al 2006). All phylogenetic studies indicated that EHMfas1 and P19-061405 generated an original cluster beside or under E. histolytica, including the PNT gene, which is known to contribute to an anomalous-shaped phylogenetic tree (Bakatselou et al 2003).…”
Section: Discussionmentioning
confidence: 99%